2006
DOI: 10.1016/j.otohns.2005.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Cervical Lymph Node Metastases in Pyriform Sinus Carcinoma

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Data from multiple pathological studies [35][36][37][38][39][40] showed that metastases form clinically N0 hypopharyngeal cancer rarely occur in levels I and IIB, and they supported the recommendation to preserve levels I and IIB in these patients, which may improve the post-operative functional outcome, particularly with regard to the spinal accessory nerve and future shoulder function [41]. Contralateral nodal clearance may also be considered in the at-risked group of patients, including those with tumor involving the medial wall of the pyriform recess [42][43][44][45], post-crioid region or the posterior wall [43,[46][47][48], and those with ipsilateral palpable nodal metastasis and clinical stage IV disease.…”
Section: Management Of the Neckmentioning
confidence: 90%
“…Data from multiple pathological studies [35][36][37][38][39][40] showed that metastases form clinically N0 hypopharyngeal cancer rarely occur in levels I and IIB, and they supported the recommendation to preserve levels I and IIB in these patients, which may improve the post-operative functional outcome, particularly with regard to the spinal accessory nerve and future shoulder function [41]. Contralateral nodal clearance may also be considered in the at-risked group of patients, including those with tumor involving the medial wall of the pyriform recess [42][43][44][45], post-crioid region or the posterior wall [43,[46][47][48], and those with ipsilateral palpable nodal metastasis and clinical stage IV disease.…”
Section: Management Of the Neckmentioning
confidence: 90%
“…Cho et al reported that in tonsil cancer, contralateral clinically N0 neck might be preserved with caution in the cases with poorly differentiated primary tumors and/or ipsilateral clinically N+ necks [10]. Aluffi et al reported that elective bilateral neck dissection is recommended in patients with locally advanced SCC of the pyriform sinus [11]. To decide when we should perform elective neck dissection during salvage surgery, we analyzed several parameters including initially advanced T stage, initially node-positive state, whether the patient had adjuvant therapy after initial treatment or not, recurrence within 1 year after initial treatment, advanced recurrent T stage, and nodal recurrence cases (Table V).…”
Section: Discussionmentioning
confidence: 99%
“…48 Aluffi P et al (2006) in their study reported that in hypopharyngeal cancers, because of the advanced stage at presentation and its extension across the midline, the risk of contralateral metastasis is high on more than 20% of cases treated surgically. 49 Varsha M Joshi et al (2014) reported that nodal staging is the most accurate prognostic factor for SCC. Unilateral nodal disease indicates a 50% reduction in long term survival while a bilateral nodal involvement indicates a 75% reduction.…”
Section: Discussionmentioning
confidence: 99%